Four Pieces of Carved Woodwork from Stirling Castle (Proceedings of the Society of Antiquaries of Scotland, 1924)
Of the original fittings and furnishings of Stirling Castle very little now remains. It is therefore of interest when fragments that have disappeared are recovered. Each of the fragments are described and illustrated. One formed part of a circular panel and is made of oak. it is decorated with the figure of a man. The second is a carving in native oak of the Scottish Lion marchant. The third and fourth are the doors of a French cabinet elaborately carved out of walnut, showing a subject in the centre framed in a heavy enriched moulding.